All-solid-state asymmetric supercapacitors based on cobalt hexacyanoferrate-derived CoS and activated carbon. Issue 11 (20th January 2017) - Subramani, K.; Sudhan, N.; Divya, R.; Sathish, M.
Abstract : All-solid-state flexible asymmetric supercapacitors fabricated using CoS and AC showed a high cell voltage, high specific capacitance, and high energy density of 5.3 W h kg −1 with excellent electrochemical stability. Abstract : All-solid-state asymmetric supercapacitors have received significant attention for being flexible, bendable, and wearable energy storage devices due to their optimum energy and power densities. Nanostructured transition-metal chalcogenides have been used as positive electrodes in the asymmetric supercapacitors due to their high theoretical capacitance, good rate capability, and excellent cycling stability. Electrochemically active dumb-bell shaped cobalt sulfide (CoS) particles were prepared via solvothermal decomposition of cobalt hexacyanoferrate (CoHCF). The dumb-bell shaped particles (2.1 to 2.7 μm in length with a lateral size of ∼1.3 μm) were formed via the self-assembly of 10–20 nm sized CoS nanoparticles. CoS exhibited a high specific capacitance of 310 F g −1 at a current density of 5 A g −1 and 95% of capacitance retention after 5000 charge–discharge cycles in a three-electrode system. An all-solid-state flexible asymmetric supercapacitor (ASC) device was fabricated using CoS and activated carbon as positive and negative electrodes, respectively. The PVA/KOH-based solid-state electrolyte offers high flexibility to the all-solid-state supercapacitor device. It exhibited a maximum cell voltage of 1.8 V with a high specific capacitance of 47 F g −1 at a current density of 2 A g −1 . Moreover, the fabricated device delivered a high energy density of 5.3 W h kg −1 and a high power density of 1800 W kg −1 with an excellent electrochemical stability of 92% even after 5000 cycles at 10 A g −1 current density. Furthermore, the solvothermal decomposition strategy for the preparation of metal sulfide could be applicable for the preparation of other metal sulfide electrode materials.